Behavioral strategies of prehistoric and historic children from dental microwear texture analysis - Estalrrich, Almudena; Krueger, Kristin L. (Frontiers in Ecology and Evolution, 2022)
Reconstructing the dietary and behavioral strategies of our hominin ancestors is crucial to understanding their evolution, adaptation, and overall way of life. Past research predominantly focused on strategies of adult individuals, leaving us to wonder the role children may have played in the community at large. Here we begin to address this by analyzing prehistoric and historic children through dental microwear texture analysis of deciduous anterior teeth. Four sample groups were used: Neandertals (N=8), prehistoric modern humans (N=14), historic Egyptians from Amarna (N=19) and historic high-Arctic Tigara from Point Hope, Alaska (N=6). Anterior deciduous teeth were carefully cleaned, molded, and cast with high-resolution materials. Labial surfaces were scanned for dental microwear textures using two white-light confocal microscopes at the University of Arkansas, and a soft filter applied to facilitate data comparisons. Results show that dental microwear texture analysis successfully differentiated the samples by all texture variables examined (anisotropy, complexity, scale of maximum complexity, and two variants of heterogeneity). Interestingly, the Neandertal and Point Hope children had similar mean values across all the texture variables, and both groups were significantly different from the Amarna, Egyptian children. These differences suggest diversity in abrasive load exposure and participation in non-dietary anterior tooth-use behaviors. Further analyses and an expanded sample size will help to strengthen the data presented here, but our results show that some prehistoric and historic children took part in similar behaviors as their adult counterparts.